Comparative Effectiveness of Lobectomy, Segmentectomy, and Wedge Resection for Pathological Stage I Non-small Cell Lung Cancer in Elderly Patients: A Population-Based Study - Zhang, Xining; Lin, Gang; Li, Jian (Frontiers in Surgery, 2021)
Introduction: This study was designed to assess the long-term survival of lobectomy, segmentectomy and wedge resection for pathological stage I non-small cell lung cancer (NSCLC) in patients over 75 years of age. Patients and Methods: Pathological stage I NSCLC patients aged ≥75 years who underwent lobectomy, segmentectomy or wedge resection were identified from the Surveillance, Epidemiology, and End Results database. Propensity-score matched and competing risks analyses were conducted. The overall survival (OS) rate and lung cancer-specific survival (LCSS) rate were compared among the three groups based on the pathological stage. Results: A total of 3,345 patients were included. In the full cohort, the OS rate and LCSS rate of lobectomy were superior to wedge resection, but not to segmentectomy, the OS advantage diminished when patients were over 85 years old or when at least one lymph node was examined during the procedure. Stratified analyses showed that there was no significant difference in OS and LCSS rates among the three surgical procedures for patients with tumors smaller than 1.0 cm. The OS and LCSS of wedge resection, not segmentectomy, were inferior to lobectomy in stage IA2-IB tumors. Conclusion: Lobectomy should be recognized as the “gold standard” procedure for pathological stage I NSCLC in patients over 75 years of age, and segmentectomy could be considered as an effective alternative. Wedge resection could be considered for patients with compromised cardiopulmonary function or tumors smaller than 1.0 cm, and intraoperative lymph node examination should be conducted.